The role of motivation in EFL students’ learning - Sisalema Baño, Luis Antonio (2023)
The purpose of this research is to know the influence of motivation in learning English as a foreign language in 10th year EFL students at the "ESCUELA ALFONSO RICARDO TROYA. The research had a mixed method approach, in such a way that it was supported by a bibliographical, field and social intervention documentary inquiry. The type of research was descriptive combined with an association of independent (Motivation) and dependent variables (Learning of students of English as a foreign language). The technique for data collection was a survey that was carried out on 34 students, this survey was developed based on a pre-test and post-test of 10 open and closed questions, with questions 1 and 4 the importance of the learning of English, while with question 5 it was known that the topics studied in class motivated the students significantly, likewise with questions 6,7 and 8 it was verified that using motivational activities increased and improved the learning of English, in In contrast to the last two questions, it was determined that the use of technological resources and attractive material motivates and creates significant learning. The analysis of the results was obtained by applying the IBM SPSS Statistics program which allowed us to understand the problem posed.